Economic growth and CO2 emissions: an investigation with smooth transition autoregressive distributed lag models for the 1800-2014 period in the USA (vol 25, pg 200, 2017) - Bildirici, Melike; Ersin, Ozgur Omer (SPRINGER HEIDELBERG, 2018)
The original publication of this paper contains a mistake.
Keywords: Environmental Sciences & Ecology